Small Glitches and Other Rotational Irregularities of the Vela Pulsar - Espinoza-Romo, C; Stepanova, M (EDP Sciences, 2021)
Context. Glitches are sudden increases in the rotation rate ν of neutron stars, which are thought to be driven by the neutron superfluid inside the star. The Vela pulsar presents a comparatively high rate of glitches, with 21 events reported since observations began in 1968. These are amongst the largest known glitches (17 of them have sizes ∆ν/ν ≥ 10−6) and exhibit very similar characteristics. This similarity, combined with the regularity with which large glitches occur, has turned Vela into an archetype of this type of glitching behaviour. The properties of its smallest glitches, on the other hand, are not clearly established. Aims. We explore the population of small-amplitude, rapid rotational changes in the Vela pulsar and determine the rate of occurrence and sizes of its smallest glitches. This will help advance our understanding of the actual distribution of glitch sizes and inter-glitch waiting times in this pulsar, which has implications for theoretical models of the glitch mechanism. Methods. High-cadence observations of the Vela pulsar were taken between 1981 and 2005 at the Mount Pleasant Radio Observatory. An automated systematic search was carried out that investigated whether a significant change of spin frequency ν and/or the spin-down rate ν takes place at any given time. Results. We find two glitches that have not been reported before, with respective sizes ∆ν/ν of (5.55±0.03)×10−9 and (38±4)×10−9. The latter is followed by an exponential-like recovery with a characteristic timescale of 31 d. In addition to these two glitch events, our study reveals numerous events of all possible signatures (i.e. combinations of ∆ν and ∆ν signs), all of them small with |∆ν|/ν < 10−9, which contribute to the Vela timing noise. Conclusions. The Vela pulsar presents an under-abundance of small glitches compared to many other glitching pulsars, which appears genuine and not a result of observational biases. In addition to typical glitches, the smooth spin-down of the pulsar is also affected by an almost continuous activity that can be partially characterised by small step-like changes in ν, ν, or both. Simulations indicate that a continuous wandering of the rotational phase, following a red spectrum, could mimic such step-like changes in the timing residuals. © ESO 2021